Incidence, clinical presentation, risk factors, outcomes, and biomarkers in de novo late acute GVHD - Akahoshi, Yu; Spyrou, Nikolaos; Hogan, William J.; Ayuk, Francis; DeFilipp, Zachariah; Weber, Daniela; Choe, Hannah K.; Hexner, Elizabeth O.; Rösler, Wolf; Etra, Aaron M.; Sandhu, Karamjeet; Yanik, Gregory A.; et al. (Blood Advances, 2023)
Late acute graft-versus-host disease (GVHD) is defined as de novo acute GVHD presenting beyond 100 days after allogeneic hematopoietic cell transplantation (HCT) without manifestations of chronic GVHD. Data are limited regarding its characteristics, clinical course, and risk factors because of underrecognition and changes in classification. We evaluated 3542 consecutive adult recipients of first HCTs at 24 Mount Sinai Acute GVHD International Consortium (MAGIC) centers between January 2014 and August 2021 to better describe the clinical evolution and outcomes of late acute GVHD. The cumulative incidence of classic acute GVHD that required systemic treatment was 35.2%, and an additional 5.7% of patients required treatment for late acute GVHD. At the onset of symptoms, late acute GVHD was more severe than classic acute GVHD based on both clinical and MAGIC algorithm probability biomarker parameters and showed a lower overall response rate on day 28. Both clinical and biomarker grading at the time of treatment stratified the risk of nonrelapse mortality (NRM) in patients with classic and late acute GVHD, respectively, but long-term NRM and overall survival did not differ between patients with classic and late acute GVHD. Advanced age, female-to-male sex mismatch, and the use of reduced intensity conditioning were associated with the development of late acute GVHD, whereas the use of posttransplant cyclophosphamide–based GVHD prevention was protective mainly because of shifts in GVHD timing. Because overall outcomes were comparable, our findings, although not definitive, suggest that similar treatment strategies, including eligibility for clinical trials, based solely on clinical presentation at onset are appropriate.
CRIS-Team Scopus Importer:2023-09-15